Effect of high intensity ultrasound on the structure and physicochemical properties of soy protein isolates produced by different denaturation methods. (December 2019) - Zheng, Ting; Li, Xiaohui; Taha, Ahmed; Wei, Yue; Hu, Tan; Fatamorgana, Pijiar Beyna; Zhang, Zhuo; Liu, Fengxia; Xu, Xiaoyun; Pan, Siyi; Hu, Hao
Abstract: The effects of high intensity (low-frequency) ultrasound (HIU, 80 W cm −2, 20 kHz for 0, 10 or 25 min) on the physicochemical properties of native, alcohol denatured and heat moisture denatured soybean protein isolates (SPI) were investigated. For the non-HIU samples, native SPI showed higher solubility, higher surface hydrophobicity and smaller particle size than those of alcohol denatured and heat moisture denatured SPI. While, heat moisture denatured SPI and its cold gel exhibited higher sulfhydryl (SH) content, denser gel and higher water holding capacity (WHC) than those of other SPI aggregates. Moreover, longer HIU changed the secondary and the tertiary structure, decreased the particle size and improved the solubility as well as surface hydrophobicity of all SPI aggregates. For native SPI, longer HIU increased the SH content, gel strength and WHC. In conclusion, HIU technology could be used to improve the physiochemical and the functional properties of SPI. Nevertheless, the physiochemical properties of SPI changed based on the isolation or denaturation methods as well as HIU time. Graphical abstract: Image 10848 Highlights: HIU improved the physicochemical and functional properties of SPI and its gels. Effects of HIU on SPI were based on the denaturation methods. Heat moisture and alcohol denaturations may lead to the aggregation of native SPI. Longer HIU changed the secondary and the tertiary structure of SPI.